Building the Future of MSMEs with Financial Inclusion and Financial Literacy - Dwi Saraswati; Ardhansyah Putra Harahap (CV. Raskha Media Group, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in national economic development as key drivers of employment and economic growth; however, they continue to face significant challenges, minimal access to formal financial services, and low levels of financial literacy. These constraints often result in weak financial management, suboptimal business decision-making, and low business performance and sustainability. This study aims to examine the role of financial inclusion and financial literacy in enhancing the sustainable performance of MSMEs. The method employed is a conceptual and descriptive review, analyzing relevant regulations, theoretical frameworks, and empirical studies on financial literacy, financial inclusion, MSME management, and business performance. The findings indicate that strong financial literacy—encompassing financial knowledge, skills, attitudes, and behaviors significantly improves MSMEs’ ability to manage cash flow, capital, investment, and business risks. Furthermore, financial inclusion, characterized by accessible, affordable, and responsible use of financial products and services, strengthens MSMEs’ capacity to expand their businesses and enhance competitiveness. The integration of financial literacy and financial inclusion contributes positively to MSME performance, as reflected in increased profitability, sales growth, market expansion, and long-term business sustainability. In conclusion, strengthening financial literacy and expanding financial inclusion are essential strategies for building a resilient and competitive future for MSMEs, and these efforts require continuous support from governments, financial institutions, and other relevant stakeholders.